Certain Properties of Fuzzy Path Connectedness and Maximal Fuzzy Path Connectedness (Journal of Bangladesh Academy of Sciences, 2018)
This paper deals with some properties of fuzzy path connectedness and maximal fuzzy path connectedness on a fuzzy topological space by means of fuzzy points.Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 67-71, 2018